Not quite dead yet : a novel [large type] - Jackson, Holly, 1992- (Random House Large Print, 2025)
"Margaret "Jet" Mason has never been able to finish anything. In her twenty-seven years, she's dropped out of school, quit a promising career, and dumped all her boyfriends. Her town's annual Halloweenfestival is a pageant of the familiar faces of friends and family, each a reminder of her failure to launch, made more surreal by the ghoulish costumes everyone's wearing. But no matter--she?s about to leave this town behind and get her fresh start somewhere else. Like with everything else, she quits the party and heads home. But as she walks in her front door, someone attacks her from behind, fracturingher skull--and leaves her for dead. Thirty-six hours later, she wakes up in the hospital to grim news: The attack has left a small bonefragment that's putting pressure on her brain?s arterial wall. The doctors tell her that a large aneurysm will soon form, and when it ruptures, the hemorrhage will be fatal. Jet has two choices: Undergo immediate surgery to remove the bone fragment, with less than a ten percent chance of survival. Or don't, and die sometime in the comingweek. With the odds stacked against her and death a foregone conclusion, Jet knows what she has to do. She has never finished anything in her life...until now. With her last remaining week, she's going to find out who murdered her."--